FERGHANA IN THE LATE BRONZE AGE AND EARLY IRON AGE (Scientific journal of the Fergana State University, 2023)
On the basis of a comparative analysis, the historiography of the Ferghana Valley of nomadic and settled cultures of the Late Bronze and Early Iron Age, collected in the region to date, and archaeological artifacts discovered during field research at new sites are highlighted. and a new approach. According to the results of the analysis, although mutual cultural contacts of nomadic and agricultural cultures were observed from the Bronze Age, only in BC. Since the middle of the 1st millennium, the processes of synthesis or assimilation between nomadic and agricultural cultures have intensified in the region.